Funkcionalna ekologija rastlin - Kermavnar, Janez (Acta silvae et ligni, 2022)
Using Slovenian forest flora as an example, we investigated four plant functional traits: specific leaf area (SLP), leaf dry matter content (VSS), plant height (VIŠ) and seed/spore mass (MAS). The first two traits define the leaf economics spectrum (way and efficiency of resource utilization), whereas the other two are linked to the size of plant organs. This study tested the correlations between plant traits and their phytoindication values for the ecological factors of light (L), temperature (T), continentality (K), soil moisture (F), soil reaction (R) and nutrients (N). We found statistically significant correlations between SLP and R, N, L, F and K; between VSS and R and N; between VIŠ and N, T, R and F; and between MAS and K, R, N and T. Along the first axis of the ordination space, we identified a leaf economics spectrum ranging from species with higher SLP values growing on more productive but also more shaded sites to plants with higher VSS values adapted to more stressful conditions (e.g. low soil reaction or low availability of nutrients and water, respectively). The VSS trait contributed the most to explaining the variability in the functional profile of forest plants, while the MAS trait contributed the least. These findings are comparable with previous studies, as the selected concepts allow for the identification of diversity of plant form and function on a global scale.
Keywords: forest vegetation; funkcionalni znaki rastlin; gozdna vegetacija; herbaceous plants; leaf dry matter content; masa semena; plant functional traits; plant height; seed mass; specific leaf area; specifična listna površina; višina rastline; vsebnost suhe snovi v listih; zelnate rastline